2002
DOI: 10.1080/10915810252866079
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Studies of Microbial Insecticide Bacillus thuringiensis var. kenyae in Rats, Rabbits, and Fish

Abstract: Bacillus thuringiensis var. kenyae (B.t.k.) is a microbial insecticide effective against lepidopteran pest species. Acute oral toxicity in rats and acute dermal toxicity, ocular irritation, skin irritation in rabbits were studied for the wettable powder formulation of B.t.k. In addition, toxicity of the wettable powder formulation was also studied in fresh water fish (Gambussia affinis). The results of these studies indicate that this wettable powder formulation of B.t.k. is nontoxic and nonirritant to rats, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
1
10
1
3
Order By: Relevance
“…A concentration-effect relationship was not observed, which means that these results are not sufficient to conclude that Cry1Ia spore-crystal is genotoxic. A similar result was observed by Meher et al (2002), showing that formulations containing Bacillus thuringiensis var. kenyae (B.t.k.)…”
Section: Resultssupporting
confidence: 85%
“…A concentration-effect relationship was not observed, which means that these results are not sufficient to conclude that Cry1Ia spore-crystal is genotoxic. A similar result was observed by Meher et al (2002), showing that formulations containing Bacillus thuringiensis var. kenyae (B.t.k.)…”
Section: Resultssupporting
confidence: 85%
“…In another study, the acute oral toxicity of GM B. thuringiensis supplemented with an additional N-acyl homoserine lactones gene were studied in Wistar rats. 37 In contrast with the findings of this study, Meher et al reported that acute oral administration of B. thuringiensis in rats has no adverse effects. 37 Previous studies also demonstrated that different doses of B. thuringiensis did not have acute toxicity following the administration in rats.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, changes in AST plasma levels suggests that the heart and skeletal muscles can had be affected by the action of Bt. However, it has been reported that biopesticides based on Bt are not toxic to fish (Jackson et al 2002, Meher et al 2002, Ahmad et al 2011. The hematocrit is a good indicator of the adverse effects of environmental factors to fish Mataqueiro 2004, Ranzani-Paiva et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that Bt has no toxicity to non-target species, including fish (Jackson et al 2002, Meher et al 2002, Ahmad et al 2011, but it produces toxic and highly specific proteins against protozoans, insects, helminths and mites of agricultural and veterinary importance (Mendozaestrada et al 2016). Thus, Bt has been recommended for control of trematodes Centrocestus formosanus in ornamental fish (Mendoza-Estrada et al 2016).…”
Section: Introductionmentioning
confidence: 99%